(untitled) (Journal of Physical Education (Maringá), 2019)
Obesity promotes a state of chronic low-grade inflammation of white adipose tissue, which is associated with different chronic diseases. While exercise induces an anti-inflammatory environment, little is known about the acute effects of continuous exercise at different intensities on inflammatory markers in obese adolescents. This study included 10 obese adolescents of both sexes, between 15 and 18 years of age. Volunteers performed two 30-minute exercise sessions. The 1st exercise session was performed at moderate intensity (55% VO2peak) and the 2nd at vigorous intensity (75% VO2peak), with a one-week interval between sessions. Blood samples were collected 10 minutes before and 20 minutes after the exercise sessions. Inflammatory markers were analyzed using the chemiluminescence method. Statistical analysis was performed using the two-factors ANOVA test for repeated measures and statistical significance was set at 5% (p <0.05). The results showed that 30 minutes of moderate aerobic exercise resulted in significant changes in circulating levels of TNF-Î± (6.23 ± 1.64 to 7.03 ± 1.49) and IL-6 (3.35 ± 1.53 to 3.85 ± 1.73). The results of this study showed that a single exercise session of moderate intensity lasting for 30 minutes induced acute responses in inflammatory markers in the obese adolescents evaluated.